2021
DOI: 10.1101/2021.11.15.468654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Niche differences, not fitness differences, explain coexistence across ecological groups

Abstract: Understanding how species interactions affect community composition is an important objective in ecology. Yet, the multitude of methods to study coexistence has hampered cross-community comparisons. Here, we standardized niche and fitness differences across 1018 species pairs to compare the processes driving composition and outcomes, among four community types (annual plant, perennial plant, phytoplankton, and bacteria/yeast). First, we show that niche differences are more important drivers of coexistence than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 104 publications
(221 reference statements)
0
8
0
Order By: Relevance
“…Second, for a non-coexisting species j we apply the methods of modern coexistence theory to the invasion growth rate of species j into this coexisting sub-community. Importantly, our new approach does not change any analysis for a community where all n species coexist and all n – 1 communities exist, which might be the majority of the existing empirical data (Buche et al ., 2022), but it does extend the applicability of the methods of modern coexistence theory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, for a non-coexisting species j we apply the methods of modern coexistence theory to the invasion growth rate of species j into this coexisting sub-community. Importantly, our new approach does not change any analysis for a community where all n species coexist and all n – 1 communities exist, which might be the majority of the existing empirical data (Buche et al ., 2022), but it does extend the applicability of the methods of modern coexistence theory.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of non-coexistence is direly needed, as often models fitted to empirical data predict competitive exclusion despite co-occurring species (Buche et al ., 2022; Germain et al ., 2016; Kraft et al ., 2015b; Godoy & Levine, 2014). This mismatch between empirical observation may stem from difficulties of assessing the actual underlying species interactions (Adler et al ., 2018a) or from uncertainties (Bowler et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, niche differences were only weakly correlated with phytoplankton or zooplankton richness. This differs from earlier findings in phytoplankton or plant communities, which mostly found that niche differences were better predictors of species richness (Narwani et al ., 2017; Buche et al ., 2021; Levine & HilleRisLambers, 2009; Adler et al ., 2010). This difference may stem from many different sources, such as model complexity, the two trophic levels in our model, or our inability to compute niche and fitness differences for all communities (see next section).…”
Section: Discussionmentioning
confidence: 99%